The Efficiency of the Maghreb Financial Markets: Tests of the Weak Form. - Sekkal Ilhem Farida, Ilhem Farida; Benbouziane, Mohammed (Finance and Business Economies Review, 2021)
The concept of efficient financial markets implies that the prices of financial assets correctly and fully reflect all available information. There are three forms of efficiency (weak, semi strong and strong). In this work, we present an empirical analysis of the weak form over a period of 10 years from 01/01/2010 to 12/31/2019 of the Maghreb financial markets (Moroccan, Tunisian and Algerian) through the monthly returns of their respective index (Masi, Tunindex and Dzairindex). For this, we used random walk tests (correlation tests, runs, stationarity and variance ratio). The advanced results are rather mixed because the stationarity tests (Dickey Fuller, Dickey Fuller Augmented and Phillips Perron) rejected this form for the three indices; correlation tests (Box-Pierce, Box - Ljung) have validated it for Masi and Tunindex; the runs test and the variance ratio test validated it for the three Maghrebian indices.